Reciprocal crosses between two populations of Trissolcus vassilievi (Mayr) (Hymenoptera: Scelionidae) reveal maternal effects on thermal phenotypes. Issue 3 (June 2015) - Iranipour, S.; BenaMolaei, P.; Asgari, S.; Michaud, J.P.
Abstract The egg parasitoid Trissolcus vassilievi (Mayr) (Hymenoptera: Scelionidae) is a significant natural enemy of the sunn pest, Eurygaster integriceps Puton (Hemiptera: Scutelleridae), the most important pest of wheat in Iran. This study examined the developmental time and egg-to-adult survival of two geographically separate populations of T. vassilievi on two corresponding host populations at five constant temperatures ranging from 15.0 to 35.0±1°C. No wasps of either population emerged at 15.0°C and the temperature threshold for development was similar between populations, ranging from 13.1±0.3 to 13.8±0.4°C for males and 12.2±0.1 to 12.6±0.1°C for females, but the thermal constant varied with gender and parasitoid population. Development of wasps from the colder Tabriz location was slower, with thermal constants for males and females of 172.6±3.1 and 204.1±1.2 degree-days, respectively, compared to Varamin wasps with 164.7±3.0 and 195.6±1.3 degree-days, respectively. Based on genetic inheritance patterns, reciprocal crosses between the two populations were expected to result in females with thermal phenotypes intermediate to their parental populations, and males that resembled their mothers. However, female progeny of crosses more closely resembled their maternal population, indicating a maternal effect on thermal phenotype. Furthermore, the magnitude of the maternal effect on the thermal constant was asymmetric and was more strongly expressed by Varmin than Tabriz females. These results suggest the possibility of using selective crosses between wasp populations, in combination with artificial selection in the laboratory, to tune the thermal phenotype of parasitoids to specific regions prior to augmentative releases.